Model Pemberdayaan dalam Wujud Edukasi Manajemen Pengelolaan Kawasan Cagar Budaya untuk Organisasi Kepemudaan Berbasis Agama di Yogyakarta - Ghifari Yuristiadhi Masyhari Makhasi; Eska Nia Sarinastiti; Fatkurrohman Fatkurrohman (Jurnal Pengabdian dan Pengembangan Masyarakat, 2019)
This article reviews descriptively the empowerment model of education of cultural heritage management in Yogyakarta for partners of two faith-based youth organizations in two sub-districts in Yogyakarta City, Yogyakarta Special Region. These two sub-districts chosen as the location of this community service because in each sub-district there is a local potential to be developed as a heritage tourism attraction. In Ngampilan, located center for souvenirs of bakpia which is a typical food of Yogyakarta, while in Kraton there is a toponym of the servants' kampongs of Yogyakarta Sultanate and other heritage building related with Yogyakarta Sultanante. Both if developed tour packages will be very worthy of selling for tourists visiting Yogyakarta. If tourists come to bakpia center Patuk is expected not only to buy souvenirs, but also to take the time to join the walking tour package to know the history of Patuk village that grows as a bakpia center, and if tourists go to Kraton not only visit Yogyakarta Palace, but also enjoy biking tours around the Kraton while knowing the names of the villages that surround the Yogyakarta Kraton complex. The two target group of people empowered were chosen because as a youth organization, it is necessary to develop productive economic activities that are beneficial to the aouthonomy of members and organizations while maintaining cultural preservation in the local environment around their homes. The program model offered in this article is tourism management training, which consists of concept design, marketing (branding and promotion) through direct and internet use, and operational implementation of heritage tourism packages based on local potential in each sub-district.